The substantialist reason in value research a critical assessment of two Inglehart theses - Lakatos, Zoltán (Socio.hu Társadalomtudományi Szemle, 2016)
Current research into values is dominated by a variable–centered paradigm that defines its inquiry as a study of substances and their impacts on each other. To illustrate the issues with this paradigm, I deconstruct Ronald Inglehart’s thesis of postmaterialist value shift and his model of culturally induced economic growth. This critique takes the field analytical perspective, a relational approach to the study of social facts that originates in the pragmatist philosophical tradition and related currents in classical sociology. The engagement with Inglehart’s thesis on value change includes a cross–cultural re–analysis of data collected within the scope of the World Values Survey. The study applies the multivariate technique of choice in field analysis, multiple correspondence analysis, which yields more consistent latent constructs than do the linear techniques used as benchmarks―and in Inglehart’s studies. Keeping to these dimensions, national values and trajectories of value change challenge Inglehart’s account on several counts. The review of Inglehart’s proposed update to the endogenous model of economic growth points out inconsistencies with the historical record of public investment in technological innovation and state intervention in general, especially with regard to the economically most developed countries. Incorporating a model using the constructs presented in the first part, this study questions Inglehart’s proposition that values have an independent effect on growth. The implications of the two critiques are developed with reference to Weber’s concept of elective affinity and Bourdieu’s studies of symbolic power. The empirical irrelevance of the culture–economy dichotomy (or symbolic versus material forms of agency) is discussed in connection with the field analytical reformulation of the challenges ahead in the sociology of values. Key words: value research, substantialism, linear models, structural equivalence, field theory, agency, symbolic power